### Math MCQ - English

# If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then

Home | Discussion Forum** If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then**

2b = a + c

a = b = c

b2 = ac

none of these

Answer : A

** View More Related Question**

** 2) A.P whose nth term is 2n-1 is**

** 3) If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then**

** 4) In a certain AP, 5 times the 5th term is equal to 8 times the 8th term, then its 13th term is equal to**

** 5) The sum of 5 numbers in AP is 30 and sum of their squares is 220. Which of the following is the third term ?**